Prebiotic and antimicrobials on performance, carcass characteristics, and antibody production in broilers - Maíra Fomentini (Ciência Rural, 2016)
To evaluate the effect of supplementation with mannan oligosaccharides, avilamycin and halquinol, alone or in combination, on the performance, carcass characteristics and antibody production in broilers (1-49 days old), male broiler chicks (n=1440; Cobb 500; one day old) were housed and distributed into a completely randomized design into six treatments (eight replicates; 30 animals per pen). To produce the experimental diets, three types of performance enhancer additives were used. Halquinol (HAL), avilamycin (AVI) and mannan oligosaccharides (MOS) were included (alone or in combination) in the basal diet (instead of corn starch). Effects of diet were observed on results of animal performance in the period 1-21 and 1-42 days old. Broilers fed with a diet without growth promoter showed lower weight gain in relation to those fed with diets with antimicrobials, MOS or a combination of them. In the period 1-49 days old, feed conversion increased in broilers fed with rations without promoter. At the end of the experimental period no influence of diets was observed on the carcass yield and cuts, and titles of specific antibodies to avian infectious bronchitis. The use of MOS and/or antimicrobials (AVI or HAL), alone or in combination, improves feed conversion of broilers reared until 49 days of age.